Development of Bahasa Indonesia Instructional in the Theme of Animal Around Me by Using Multimedia Animation Based Learning for Students with Hearing Impairment - Angger Timansah; Sri Joeda Andajani; Asri Widjiastuti (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2019)
Implementation of learning with the theme of animals around me has a problem that is hearing impairment students in class IV do not understand what the names and concepts of animals in the environment, so that, in daily life, the students can not interact with the surrounding environment properly. As a result, the learning outcomes is low. Therefore, it needs an innovative and creative learning. The purpose of this study is to produce a multimedia animation based learning prototype of Bahasa Indonesia materials with the theme of animal around me for hearing impairment students. This research development using the Borg and Gall (2007) development model was carried out in 9 stages due to limited time and cost, namely: (1) identification (2) analysis (3) analyzing problems (4) research objectives (5) instrument assessment (6) strategy (7) developing teaching materials (8) Selecting themes (9) Expert validation. Data collection used questionnaires, pretest and posttest. The results of data collection techniques is the feasibility of teaching materials based on multimedia learning animation for hearing impairment students. The results of the Z sign test analysis showed that 2.202 were greater than the critical value α = 5%, namely 1.96, it could be analyzed that there was effectiveness in terms of the level of mastery of bahasa Indonesia teaching materials with the themes of animal around me based on multimedia animation learning in SDLB Negeri Tompokersan Lumajang.